FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENGGUNAKAN BENIH UNGGUL HIBRIDA VARIETAS MELATI PADA USAHATANI PADI (Oryza sativa L) SAWAH TADAH HUJAN DI DESA SABAHLIOH. (JASEP, 2020)
Factors Affecting Farmers' Decisions Using Superior Seed Hybrid Jasmine Varieties on Rice Farming Oryza sativa L Rainfed Rice Fields i Village S Abahlioh District Mayang Flower District OKU East Research this aim for Analyze factors that affect decision farmers use hybrid varieties hybrid superior seeds . Research this held in Sabahlioh Village, Bunga Mayang District, East OKU Regency . Data Collection Research do with method survey which used a sample of 40 samples. Sampling method used in this research is random layered not balanced . Data processing method using binary logistic regression analysis. Hacil research this could concluded that is Factors - factors that influence real in decision farmers use seed superior hybrid varieties jasmine in Village Sabahlioh districts Flower Ma who East OKU District that is production (X1 ), wide land (X2), price seed (X3). While price rice (X4) no take effect on real to decision farmers use seed superior hybrid varieties jasmine in Village Sabahlioh districts Flower Mayang East OKU District. Keywords: factors, decisions, hybrid superior seeds